(untitled) (Advances in Knowledge Representation, 2022)
Intangible assets are the foundation of the information and knowledge economy, and measuring them is the task of the Intellectual Capital study area. Investors, business executives, professionals, government authorities, and academics engage in extensive discussion over Intellectual Capital’s capacity to generate value. Due to the variety of models, definitions, and aspects that comprise this scientific discipline, it has not yet been feasible to establish a fundamental framework that connects the reasons for measuring Intellectual Capital in companies. In this regard, the purpose of this study is to uncover the elements that influence the determination of the reasons why organizations assess this intangible asset. This is a descriptive exploratory study that uses Content Analysis to understand these characteristics using a Systematic Literature Review. Consequently, the identification of objectives is offered as a determinant for proposing more effective approaches for the assessment of Intellectual Capital in businesses. The conclusion is that addressing these factors tends to foster imperative advances in the design of strategy planning and execution, the exercise of daily organizational decision-making, the production of organizational value and competitive advantage, and the assurance of consistent non-financial information. Suggestions for future research include expanding the study to additional bases, gaining the opinion of professionals about other elements, and developing models geared toward these factors.